The Model of Green Behavioural Intention Among Women Entrepreneur: A Quantitative Study - Asyiffa Fitri Awallia; Melia Famiola (Indonesian Journal of Business and Entrepreneurship (IJBE), 2021)
Today, business activities seem to have shifted towards green business with the inception of women entrepreneurs who are more environmentally conscious. This study aims to examine the behaviour construction of women entrepreneurs' intention towards green business in Indonesia. Using a quantitative approach, data were collected from 122 women entrepreneurs using simple random sampling, which were then processed by PLS-SEM. This study found that green behavioural intention among women entrepreneurs in Indonesia reflects their environmental concern with a strong solid vision to create the change. The argument that market rationality will mediate green business behaviour and predicted as a barrier factor to their intention of having business with environmental concerns was not proven. This study argues that women entrepreneurs with green business initiatives in Indonesia belong to the visionary champion type, an entrepreneur who takes themselves as agents of change. Increasing the number of women entrepreneurs with green business initiation in Indonesia will favour Indonesia's future economy and sustainability. The nurture of women's role in spreading knowledge allows them to create their market by educating the market with their green image and offering alternatives. The government needs to pay strict attention and formulate policies on encouraging women entrepreneurs in Indonesia, particularly those starting their business with environmental consciousness. Keywords: women entrepreneurs, green business, behavioural intention, sustainable development goals, Indonesia